1970
DOI: 10.1029/jb075i023p04396
|View full text |Cite
|
Sign up to set email alerts
|

Tenoumer Crater, Mauritania: Age and petrologic evidence for origin by meteorite impact

Abstract: Inclusions of granitic basement rocks, collected from the sparse ‘lava’ exposed at the 1.8‐km‐diameter Tenoumer crater, Mauritania, exhibit distinctive petrographic features considered indicative of shock‐wave action and diagnostic for meteorite impact. The observed effects include (1) distinctive planar features in quartz, oriented parallel to ω{ 101¯3 } and to other specific planes; (2) intense selective vesiculation of quartz and felspar grains; (3) presence of lechatelierite apparently formed by fusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

1970
1970
2019
2019

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 17 publications
1
43
1
Order By: Relevance
“…6c and 6d) was found in some of the thin sections. Similarly textured ballen quartz has been found in impact glasses and crystalline impact melts of many impact craters (e.g., French et al 1970;Engelhardt 1972;Carstens 1975;Dressler et al 1997). This ballen quartz has been interpreted to represent pseudomorphs after cristobalite, which, in turn, is thought to have replaced lechatelierite, originally formed by shock-induced melting of quartz (Carstens 1975), or to represent recrystallized diaplectic quartz glass that underwent transition to cristobalite and then α-quartz (Bischoff and Stöffler 1981;1984).…”
Section: Shock Metamorphismmentioning
confidence: 99%
“…6c and 6d) was found in some of the thin sections. Similarly textured ballen quartz has been found in impact glasses and crystalline impact melts of many impact craters (e.g., French et al 1970;Engelhardt 1972;Carstens 1975;Dressler et al 1997). This ballen quartz has been interpreted to represent pseudomorphs after cristobalite, which, in turn, is thought to have replaced lechatelierite, originally formed by shock-induced melting of quartz (Carstens 1975), or to represent recrystallized diaplectic quartz glass that underwent transition to cristobalite and then α-quartz (Bischoff and Stöffler 1981;1984).…”
Section: Shock Metamorphismmentioning
confidence: 99%
“…Almost identical rock types have been found at some terrestrial impact structures. At the Tenoumer structure in Mauritania, inclusions of shocked granite are held in what has been interpreted (French et al, 1970) as an impact, melt, formed by fusion of the target rock and injected along with the fragments into crater wall fractures. Cooling of this melt-fragmental mixture produced a texture (Fig.…”
Section: Evidence For Shock Damage In the Lunar Samplesmentioning
confidence: 99%
“…On the basis of the occurrence of small dikes, which were supposed to be rhyodacitic lava, Monod and Pomerol (1966) suggested a possible volcanic origin for the structure. Finally, definitive evidence for the impact origin of this crater was supplied by French et al (1970), who found up to eight sets of planar deformation features (PDFs) in quartz grains in inclusions of granitic basement scattered throughout the above-mentioned "lava." Following this discovery the nature of this "lava" was reevaluated by the same authors and interpreted as rapidly quenched impact melt rock.…”
Section: Introductionmentioning
confidence: 99%